The Sponsor's Fight for Audience: How General Foods Promoted Listenership for the Byrd Expedition Broadcasts. Issue 2 (3rd July 2017) - Perry, Stephen D.
Abstract : This study examines stunting, gimmickry, and the use of guest appearances to attract, keep, and rebuild an audience for the Byrd Expedition broadcasts, aired on CBS, between 1933 and 1935. The sponsor worked to maximize the benefit its product received through program association by attracting the largest audience possible. This research suggests a reconsideration of where rivalry existed in the sponsorship era of broadcasting. It finds that hype through stunts and gimmicks helped keep the expedition exciting during low exploring times. Notable guests were included in the program when convenient but not necessarily during times of low levels of adventure.